Survey on Public Behaviours Toward Online Shopping During COVID-19 in Negeri Sembilan - Soo, Mee Eng; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2022)
The spreading of the coronavirus 2019 (COVID-19) caused significant impacts to Malaysia’s economy such as the decline in the gross domestic product, the value of Malaysian ringgit decreased, increasing the unemployment rate, and bankruptcies in different major industries. Small and medium-sized enterprises (SMEs) had to deal with lockdown limitations like all business premises required to close during the MCO period, which had an impact on their operations and income. Hence, e-commerce plays a vital role to help SMEs expand their business. SMEs may not understand the current public behaviours towards online shopping. Therefore, this study is conducted to identify the public behaviours towards online shopping in Negeri Sembilan during the COVID-19 pandemic. An online questionnaire form was distributed to social media using the convenience sampling method. Furthermore, this research study the factors affecting public purchase online, public satisfaction towards online shopping services, and changes in public purchasing behaviours during the COVID-19 pandemic. The methods applied in this study are the descriptive analysis, Friedman test, Spearman’s correlation test, Chi-squared test, and Cramer’s V analysis. The results show that the public is usually purchase once per month and prefer to purchase fashion and clothing products which paid by using bank transfer. The main factor that affects the public to purchase online is convenience. Overall, the public is satisfied with the online shopping services and there are some changes in public purchasing behaviours during the COVID-19 pandemic. There is an association between respondent’s occupation and public satisfaction towards online shopping services, and between respondent’s education level and changes in public purchasing behaviours.  The suggestion for future researchers is to increase the sample size to more states in Malaysia to improve the completeness of the study.